Grain refinement, microhardness distribution, strain hardening behaviour and mechanical proprieties of RD-ECAPed AA 1050 - Halimi, A.; Hemmouche, L.; Chettah, I.E.; Louchene, Z.A. (Archives of Mechanics, 2023)
This study aims to investigate the evolution of mechanical and microstructural characteristics of the 1050 aluminium alloy processed by Rotary Die Equal Channel Angular Pressing (RD-ECAP). The RD-ECAPed specimens were analysed after each pass using optical microscopy, quasi-static compression test and microhardness measurements. The results revealed a reduction in grain size from 29 μm before the RD-ECAP process to a minimum value of 2 μm at the second pass, corresponding to the maximum value of compressive yield strength, reaching 184 MPa. Furthermore, there was an increase in hardness from 30 Hv to 63 Hv with a homogeneous distribution along the longitudinal surface, especially in the initial four RD-ECAP passes. Additionally, the appearance of a 45° shear plane was observed at the last fifth pass, coinciding with the region of maximum microhardness.